Nitrite levels in Philippine Sweet Bacon (tocino) sold in Metro Manila - Parra, Adrianne Fritz D.
This study determined the residual nitrite levels of tocino sold in supermarkets and wet markets in Metro Manila in 2019 using the AOAC Method 973.31 or the Colorimetric Method for Nitrite Analysis. The study also established: practices of small- and micro-scale processors of tocino, generation of physico-chemical properties, such as color and water activity, of tocino, generation of nitrite level and salt content of curing salts, and determination of possible relationships among the variables presented. Generation of residual nitrite data reported minimum and maximum values of tocino samples from the supermarkets were 0.015±0.000 and 500.07±8.27 mg NO2/ kg tocino, respectively; while from wet markets were 0.36±0.49 and 25.30±35.76 mg NO2/ kg tocino, respectively. It was found that the samples were below the maximum allowable level of 80 mg NO2/ kg for nitrite cured meat (CODEX STAN 192-1995), except two commercially brands from the supermarkets with levels of 139.136±3.23 and 500.07±8.27 mg NO2/ kg tocino. Survey of the practices showed traditional methods of curing tocino still prevails in wet markets. Variation among the physico-chemical properties of the tocino samples was observed. Water activity values were ≤0.95. The values of nitrite levels of curing salts were 7,047.943±1837.920 and 21,706.125±3343.076 mg NO2/ kg curing salt and their salt contents were 98.0% NaCl + 2.0% NaNO2 and 98.7% NaCl + 1.3% NaNO2. The study found that all the factors, practices of tocino processors, physico-chemical properties of tocino and curing salt contributed to the varying residual nitrite levels in tocino. Further, relationship between L* and a* values (p<0.05) was inversely correlated. This has significant effect on the storage conditions of tocino where an increase in the lightness would imply lowering of the redness of the meat product.